Assessment of Fidelity in Interventions to Improve Hand Hygiene of Healthcare Workers: A Systematic Review. (10th February 2016) - Musuuza, Jackson S.; Barker, Anna; Ngam, Caitlyn; Vellardita, Lia; Safdar, Nasia
Abstract : OBJECTIVE: Compliance with hand hygiene in healthcare workers is fundamental to infection prevention yet remains a challenge to sustain. We examined fidelity reporting in interventions to improve hand hygiene compliance, and we assessed 5 measures of intervention fidelity: (1) adherence, (2) exposure or dose, (3) quality of intervention delivery, (4) participant responsiveness, and (5) program differentiation. DESIGN: Systematic review METHODS: A librarian performed searches of the literature in PubMed, Cumulative Index to Nursing and Allied Health (CINAHL), Cochrane Library, and Web of Science of material published prior to June 19, 2015. The review protocol was registered in PROSPERO International Prospective Register of Systematic Reviews, and assessment of study quality was conducted for each study reviewed. RESULTS: A total of 100 studies met the inclusion criteria. Only 8 of these 100 studies reported all 5 measures of intervention fidelity. In addition, 39 of 100 (39%) failed to include at least 3 fidelity measures; 20 of 100 (20%) failed to include 4 measures; 17 of 100 (17%) failed to include 2 measures, while 16 of 100 (16%) of the studies failed to include at least 1 measure of fidelity. Participant responsiveness and adherence to the intervention were the most frequently unreported fidelity measures, while quality of the delivery was the most frequently reported measure. CONCLUSIONS: Almost all hand hygiene intervention studies failed to report at least 1 fidelity measurement. To facilitate replication and effective implementation, reporting fidelity should be standard practice when describing results of complex behavioral interventions such as hand hygiene. Infect Control Hosp Epidemiol 2016;37:567–575